WHEN THYROID STIMULATING HORMONE AND FREE THYROXINE MISMATCH: A CASE REPORT - Fong , Yeap Cai; Lordudass, Alexis (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Thyroid hormone resistance (THR) is characterized by lack of end-organ responsiveness to thyroid hormone with high serum free thyroxine (FT4) with inappropriately high thyroid stimulating hormone (TSH). CASE We report a 3-month-old male, born term via spontaneous vaginal delivery was referred to us at day 13 of life for inappropriately high TSH: 7.69 mIU/L (NV: 0.39–7.0) and high FT4: 57.5 mIU/L (NV: 8.7–16.2). His birth weight was 3.5 kg. Antenatally, his mother has no thyroid disorder. He is the only child of non-consanguineous parents. The cord TSH was 22.01 mIU/L. At day 3 of life, TSH was 15 mIU/L and FT4 was insufficient. At day 23 of life, thyroid function test (TFT) revealed TSH: 6.29 mIU/L, FT4: 47.9 pmol/L and free triiodothyronine (FT3): 6.6 pmol/L (NV: 3.1–10.6). Clinically he had persistent left parieto-occipital swelling and tachycardia. He was started on carbimazole (0.1 mg/kg/day) at 2 months of life. Thyroid autoantibodies were negative with anti-TSH receptor (TRAb) <0.8 IU/L (NV: <1.75), anti-thyroid peroxidase <9 IU/ml (NV: <35) and antithyroglobulin 14 IU/mL (NV: <115). Pituitary hormones taken on day 76 of life revealed prolactin 1,553.2 mIU/L (NV: 70.81–566.64) with mini puberty (testosterone: 4.3 nmol/L, FSH: 1.8 IU/L and LH: 3.3 IU/L). At day 82 of life, prolactin was normal at 322 mIU/L and IGF-1 at 45.6 ng/ml (NV: 27-157). FBC, renal profile and liver function test were normal. Skull x-ray revealed no calcification and cranial ultrasound was normal. During follow-up, he has normal developmental milestones, weight: 5.3 kg (25th percentile), length: 55 cm (2nd percentile) and COH: 40 cm (75th percentile). Genetic confirmation testing is pending while awaiting funds. We plan to stop Carbimazole during follow-up. CONCLUSION We started carbimazole for tachycardia and suspicion of craniosynostosis. Treatment for THRB is not needed mostly, because the hyposensitivity to thyroid hormones seems to be adequately compensated by the increase in secretion of T4 and generation of T3.